A Discussion of Malware Attacks Targeting Smart Homes and Connected Devices: Investigating Cybersecurity Risks in Everyday Living - I Gede Adnyana; Emmy Febriani Thalib; Mariano Alan Harum; Martha Apriliani Chionia Nagas; Martinus Wilfrid Jawa (Journal of Digital Law and Policy, 2023)
Computer technology has advanced with the digital age. Software for several platforms is crucial to streamlining human work with computers. This software is essential for many user tasks, including IoT ones. Through data exploitation and communication technologies, the Internet of entities (IoT) connects physical and virtual entities to the global web. This technology aims to make it easier for humans to interact with objects and let them communicate. In daily life, numerous specialized gadgets use the Internet of Things (IoT), especially Smart Homes. Smart Homes integrate networked communication networks with home devices for remote control, monitoring, and access. The name "Smart" in Smart Homes suggests intelligence, however IoT devices have limitations. Malware is purposely designed to disrupt or gain unauthorized access to computer systems without the system owner's knowledge or agreement. Malware threatens smart home security widely. Malware can also quickly regenerate and adapt as technology advances. It's often integrated into popular online apps. This study examines how malware assaults affect IoT and Smart Home devices. The study's conclusions include an analytical report on IoT and Smart Home malware mitigation in legal perspectives.